The potential applications of Apolipoprotein E in personalized medicine - Villeneuve, Sylvia; Brisson, Diane; Marchant, Natalie L.; Gaudet, Daniel (Frontiers in Aging Neuroscience, 2014)
Personalized medicine uses various individual characteristics to guide medical decisions. Apolipoprotein (ApoE), the most studied polymorphism in humans, has been associated with several diseases. The purpose of this review is to elucidate the potential role of ApoE polymorphisms in personalized medicine, with a specific focus on neurodegenerative diseases, by giving an overview of its influence on disease risk assessment, diagnosis, prognosis and therapy. This review is not a systematic inventory of the literature, but rather a summary and discussion of novel, influential and promising works in the field of ApoE research that could be valuable for personalized medicine. Empirical evidence suggests that ApoE genotype informs pre-symptomatic risk for a wide variety of diseases, is valuable for the diagnosis of type III dysbetalipoproteinemia, increases risk of dementia in neurodegenerative diseases, and is associated with a poor prognosis following acute brain damage. ApoE status appears to influence the efficacy of certain drugs, outcome of clinical trials, and might also give insight into disease prevention. Assessing ApoE genotype might therefore help to guide medical decisions in clinical practice.